RIP1/RIP3/MLKL Mediates Myocardial Function Through Necroptosis in Experimental Autoimmune Myocarditis - Wu, Yujing; Zheng, Zhenzhong; Cao, Xiantong; Yang, Qing; Norton, Vikram; Adini, Avner; Maiti, Amit K.; Adini, Irit; Wu, Hao (Frontiers in Cardiovascular Medicine, 2021)
Cardiomyopathy often leads to dilated cardiomyopathy (DCM) when caused by viral myocarditis. Apoptosis is long considered as the principal process of cell death in cardiomyocytes, but programmed necrosis or necroptosis is recently believed to play an important role in cardiomyocyte cell death. We investigated the role of necroptosis and its interdependency with other processes of cell death, autophagy, and apoptosis in a rat system of experimental autoimmune myocarditis (EAM). We successfully created a rat model system of EAM by injecting porcine cardiac myosin (PCM) and showed that in EAM, all three forms of cell death increase considerably, resulting in the deterioration of cardiac conditions with an increase in inflammatory infiltration in cardiomyocytes. To explore whether necroptosis occurs in EAM rats independent of autophagy, we treated EAM rats with a RIP1/RIP3/MLKL kinase-mediated necroptosis inhibitor, Necrostatin-1 (Nec-1). In Nec-1 treated rats, cell death proceeds through apoptosis but has no significant effect on autophagy. In contrast, autophagy inhibitor 3-Methyl Adenine (3-MA) increases necroptosis, implying that blockage of autophagy must be compensated through necroptosis. Caspase 8 inhibitor zVAD-fmk blocks apoptosis but increases both necroptosis and autophagy. However, all necroptosis, apoptosis, and autophagy inhibitors independently reduce inflammatory infiltration in cardiomyocytes and improve cardiac conditions. Since apoptosis or autophagy is involved in many important cellular aspects, instead of suppressing these two major cell death processes, Nec1 can be developed as a potential therapeutic target for inflammatory myocarditis.